The Earthy Nature of the Bible - Boer, R. author. aut Link
X, 196 p.
Keywords: Through a series of close readings, Boer explores the earthy nature of the Bible. These readings are gathered into three parts: the Song of Songs; Masculinities; Paraphilias. Each study is undertaken with rigorous attention to relevant scholarship and significant theoretical engagement (especially with psychoanalysis, ecocriticism and Marxism).